2008 IEEE International Conference on Software Maintenance 2008
DOI: 10.1109/icsm.2008.4658103
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis on distribution patterns of software maintenance effort

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Their results show that the design phase is the most expensive, consuming about 38% of total effort, while the analysis and implementation phases account for small proportions, about 11% each. These results are somewhat contrary the results reported in Yang et al's [32]. A more recent study reported by the same authors (De Lucia et al) presents estimation models and the distribution of effort from a different project in the same organization [14].…”
Section: Related Workcontrasting
confidence: 64%
See 1 more Smart Citation
“…Their results show that the design phase is the most expensive, consuming about 38% of total effort, while the analysis and implementation phases account for small proportions, about 11% each. These results are somewhat contrary the results reported in Yang et al's [32]. A more recent study reported by the same authors (De Lucia et al) presents estimation models and the distribution of effort from a different project in the same organization [14].…”
Section: Related Workcontrasting
confidence: 64%
“…The study provides evolutional trends on the relative effort distribution of four technical phases (analysis, design, implementation, and test) across four versions of the project, showing that the proportion of implementation effort tends to decrease from the first version to the forth, while the proportion of analysis effort follows a reversed trend. Similarly, Yang et al [32] present results from an empirical study on the effort distribution of a series of 9 projects delivering respective 9 versions a software product. All projects are maintenance type except the first project which delivers the first version of the series.…”
Section: Related Workmentioning
confidence: 99%
“…Though most are medium, small-sized software organizations and companies, the application domains come across telecommunication, financial, government, energy, education, etc. Existing research and reports has reported its effectiveness in several cases [24][25][26].…”
Section: B Software Process Management Toolsmentioning
confidence: 96%
“…To achieve acceptable quality, software project teams devote a substantial portion of the total development effort to perform testing. According to industry reports, software testing consumes about 10-25% of the total project effort, and on some projects this number may reach 50% [1].…”
Section: Introductionmentioning
confidence: 99%